Ketahanan Ekonomi Pada Masa Pandemi Covid-19 Ditinjau dari Aspek Modal Sosial dan Motivasi Masyarakat Manggarai Barat, Labuan Bajo, Nusa Tenggara Timu (pp. 203-224) - Mohamad Axel Putra Hadiningrat; Gumilar Rusliwa Somantri; Chotib Chotib; Beti Nurbaiti (Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to analyze aspects of social capital and motivation of the people of West Manggarai in Labuan Bajo, East Nusa Tenggara related to achieving prosperity during the Covid-19 pandemic. The research was conducted from July 24 to August 2, 2022, on a total of 300 respondents in that location, using a structured questionnaire and equipped with in-depth interviews. The data was further processed to produce descriptive statistical analysis and the results of Structural Equation Modelling (SEM) using Lisrel software. The results of the study conclude that there is a positive correlation between social capital and motivation partially with economic resilience.